Mechanically induced structural changes during dynamic compression of engineered cartilaginous constructs can potentially explain increases in bulk mechanical properties. - NAGEL, THOMAS; KELLY, DANIEL (My University, 2012)
Several studies on chondrocyte seeded hydrogels in bioreactor culture report increased mechanical properties of mechanically loaded constructs compared to unloaded free swelling controls despite no significant differences in biochemical composition. One possible explanation is that changes in the collagen architecture of dynamically compressed constructs lead to improved mechanical properties. Collagen molecules are incorporated locally into the extracellular matrix with individual stress-free configurations and orientations. In this study we isolated and computationally investigated possible influences of loading on the collagen architecture in chondrocyte seeded hydrogels and their resulting mechanical properties. Both the collagen orientation and its stress-free configuration were hypothesised to depend on the local mechanical environment. Reorientation of the collagen network alone in response to dynamic compression leads to a prediction of constructs with lower compressive properties. In contrast, remodelling of stress-free configurations of collagen fibres was predicted to result in compacted tissues with higher swelling pressures and an altered pre-stressed state of the collagen network. Combining both mechanisms resulted in predictions of construct geometry and mechanical properties in agreement with experimental observations. This study provides support for the hypothesis that structural changes to the collagen network contribute to the enhanced mechanical properties of cartilaginous tissues engineered in bioreactor culture.
PUBLISHED
Keywords: mechanobiology; collagen remodelling; natural configuration; bioreactor; chondrocytes; mechanobiology; collagen remodelling; natural configuration; bioreactor; chondrocytes; Next Generation Medical Devices